Implementation of the Tangerang Cerdas Policy by the Tangerang City Government - Jaenudin, Riqi Adinugraha (GoAcademica Research & Publishing, 2024)
In Tangerang City, the number of children out of school at the elementary school level is 19,067 people, this is one of the reasons for the launch of Tangerang Cerdas to provide scholarship assistance in the form of cash to meet the costs of school needs so that the number of children out of school continues to decrease every year. This research aims to describe the implementation of the Tangerang Cerdas Policy. The research method used is a qualitative description using observational study data analysis and in-depth interviews. The results of the research that has been carried out show that the implementers have implemented Tangerang Cerdas but it has not been optimal, in 2020-2021 in each semester more than 6,000 children have received Tangerang Cerdas assistance at the elementary school level in all areas in Tangerang City. However, there are still many who have not received assistance because there are budget limitations and there are also process stages and terms and conditions that apply to receive Tangerang Cerdas assistance. The important role of staff at schools or schools in collecting data and submitting it to the Tangerang Smart Center is one of the keys to success, so there needs to be a budget for staff who look for data at each school to be more motivated in their work.